What makes the pipeline leak? Women’s gender-based rejection sensitivity and men’s hostile sexism as predictors of expectations of success for their own and the respective other gender group - Ollrogge, Karen; Roswag, Malte; Hannover, Bettina (Frontiers in Psychology, 2022)
In academia, the proportion of women decreases with each career level. In our research, we examined how this so-called leaky pipeline relates to gender-based relative expectations of success, i.e., what chances of success women and men students assume for their own gender group relative to the respective other gender group. Our research participants were students from the social sciences where women are the majority among students, such that it is more readily – but erroneously – inferred that gender discrimination is not an issue. We assumed that gender-based relative expectations of success should be predicted by two variables that matter in different ways to men and women. Women students should experience higher gender-based rejection sensitivity than men students, with gender-based rejection sensitivity mitigating relative success expectations in women, but not in men. Men students should exhibit higher hostile-sexist attitudes toward women than women students, with hostile sexism reducing men students' but not women students' relative success expectations. We tested our hypotheses in an (under-)graduate sample of women and men students enrolled in educational or psychological majors (N = 444). Results suggest that women are more concerned about being treated differently because of their gender than men and men hold more sexist attitudes towards women than women do, with gender-based rejection sensitivity contributing to women students' and sexism to men students' expectation that their own gender group will less likely succeed in their aimed for future job. Implications how the leaky pipeline can be patched are discussed.